PENINGKATAN PEREKONOMIAN PETANI MELALUI MARKETING DIGITAL - Feriady, Anton; Saputera, Surya Ade; Selviani, Ayudho (JURNAL ABDIMAS SERAWAI, 2024)
ABSTRACT Muara Pulutan Village is a village that has great potential in the agricultural sector. However, farmers in this village still experience difficulties in marketing their products, resulting in low income. For this reason, community service activities are carried out with the aim of increasing farmers' income through digital marketing. This activity is carried out by providing training to farmers on how to use social media and marketplaces to market their products. Apart from that, farmers are also assisted in creating attractive product photos and videos and writing informative product descriptions. The results of this activity show that farmers in Muara Pulutan Village have been able to use social media and marketplaces to market their products. This results in an increase in their income. Keywords: Muara Pulutan Village, farmers, digital marketing, social media, marketplace, income